2009
DOI: 10.1016/j.jml.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Letter-transposition effects are not universal: The impact of transposing letters in Hebrew

Abstract: We examined the effects of letter transposition in Hebrew in three masked-priming experiments. Hebrew, like English has an alphabetic orthography where sequential and contiguous letter strings represent phonemes. However, being a Semitic language it has a non-concatenated morphology that is based on root derivations. Experiment 1 showed that transposed-letter (TL) root primes inhibited responses to targets derived from the non-transposed root letters, and that this inhibition was unrelated to relative root fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 60 publications
12
66
1
Order By: Relevance
“…The present data add further evidence to the view that lexical space in Semitic languages is defined by root families, so that "all words derived from a given root are clustered together" (Velan & Frost, 2007, p. 916; see also Frost et al, 2005;Velan & Frost, 2009). Given that transposed-letter priming with word primes does not occur in the absence of a morphological/semantic relationship-as was shown in Experiment 1 when primes and targets were derived from different roots (see also Duñabeitia et al, 2009, for evidence in Spanish)-the stitution neighbors was 7.9 (range, 1-25).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The present data add further evidence to the view that lexical space in Semitic languages is defined by root families, so that "all words derived from a given root are clustered together" (Velan & Frost, 2007, p. 916; see also Frost et al, 2005;Velan & Frost, 2009). Given that transposed-letter priming with word primes does not occur in the absence of a morphological/semantic relationship-as was shown in Experiment 1 when primes and targets were derived from different roots (see also Duñabeitia et al, 2009, for evidence in Spanish)-the stitution neighbors was 7.9 (range, 1-25).…”
Section: Discussionsupporting
confidence: 72%
“…These words were preceded by prime words that were (1) It has been proposed that lexical space in Semitic languages is not organized in orthographic terms, as in Indo-European language, the reason being that, in Semitic languages, lexical space would be organized according to root families (Frost, 2009). Consistent with this hypothesis, Velan and Frost (2009) showed that when the root letters of a nonword prime are transposed in Hebrew, the transposed-letter priming effect found in Indo-European languages is absent. In their Experiment 3, response times (RTs) to a target word such as mdrgh, whose root is d.r.g, were similar when the prime was the transposed-letter nonword prime mrdgh, which has the nonexisting root r.d.g, and when the prime was a replacement-letter nonword prime in which two letters from the root were replaced; furthermore, a condition that employed a transposed-letter root prime (mgrdh, a word that is derived from the existing root g.r.d ) showed a small (11-msec) inhibitory effect, relative to the replacement-letter condition.…”
Section: Experiments 1 Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…3 Thus, the present data suggest that the stage of letter/mora position coding is-to some degree-language independent. We acknowledge, however, that factors such as visual format (as Korean Hangul; see Lee & Taft, 2009) or the morphological characteristics of a given language (e.g., the ordering of the root letters in Semitic languages; Velan & Frost, 2009; see also Perea, Abu Mallouh, García-Orza & Carreiras, 2010) may influence the process of letter position coding.…”
Section: Discussionmentioning
confidence: 99%